Correlational between: Biological literacy and metacognitive abilities with critical thinking in junior high school students - N. Najmah; R. Rusdi; Rizhal Hendi Ristanto (University of Muhammadiyah Malang, 2024)
Facing the 21st century which is an educational challenge requires schools to be able to produce students who have biological literacy skills, metacognitive skills and critical thinking skills. The study aims to analyze the relationship between biological literacy skills and critical thinking, analyze the relationship between metacognitive abilities and critical thinking, and analyze the relationship between biological literacy skills and critical thinking. metacognitive abilities with critical thinking. The research was conducted at Public Junior High School 3 Parungpanjang, Bogor. The research sample consisted of 150 class VII students consisting of 8 classes. Critical thinking skills are measured using a critical thinking instrument in the form of essay questions from 6 aspects of critical thinking. Biological literacy is measured using multiple choice questions with 4 levels of biological literacy dimensions. Metacognitive ability is measured using an essay question metacognitive ability instrument developed from 3 metacognitive aspects. The test results show that the average student's biological literacy ability is in the medium category, the student's metacognitive ability is sufficient and the student's critical thinking ability is high. There is a significant relationship between biological literacy and critical thinking but there is no relationship between metacognitive ability and critical thinking, and there is a mutual relationship between biological literacy, metacognitive ability and critical thinking with a correlation value of 0.444 (medium correlation).